2009
DOI: 10.1159/000201572
|View full text |Cite
|
Sign up to set email alerts
|

The Ile646Val (2073A>G) Polymorphism in the Kinase-Binding Domain of A-Kinase Anchoring Protein 10 and the Risk of Colorectal Cancer

Abstract: Objective: The purpose of this study is to investigate whether the Ile646Val (2073A>G) polymorphism in the kinase-binding domain of A-kinase anchoring protein 10 (AKAP10) is related to the risk of colorectal cancer (CRC), clinicopathological variables and the environmental factors for the development of CRC. Methods: Applying TaqMan allelic discrimination, we investigated AKAP10 Ile646Val (2073A>G) polymorphism in 288 Chinese CRC patients and 281 healthy controls. Results: Logistic regression analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…The studies of 787 familial breast cancer patients and 993 controls showed that the Ile646Val polymorphism of AKAP10 was associated with an increased familial breast cancer risk [12]. In a previous case-control study, we firstly found that the Ile646Val polymorphism of AKAP10 was significantly associated with colorectal cancer risk [13].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The studies of 787 familial breast cancer patients and 993 controls showed that the Ile646Val polymorphism of AKAP10 was associated with an increased familial breast cancer risk [12]. In a previous case-control study, we firstly found that the Ile646Val polymorphism of AKAP10 was significantly associated with colorectal cancer risk [13].…”
Section: Discussionmentioning
confidence: 96%
“…The TaqMan RT-PCR targeted for AKAP10 A-2073G polymorphism was performed according to previous description [13]. Primers and TaqMan probes were purchased from Invitrogen Biotechnology …”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…AKAP10 is the kinase-anchoring gene 10 which is currently an identifier for determining the risk of developing colorectal cancer (Wang et al, 2009a;Wang et al, 2009b). It also requires cAMP to diffuse through the cytoplasm to propagate its signal.…”
Section: Other Cellular Processesmentioning
confidence: 99%
“…12 Subsequently, further studies confirmed the 'deleterious' effect of the G1936 variant with associations with familial breast cancer, 13 increased basal heart rate and decreased heart rate variability 14,15 and increased risk of colorectal cancer. 16 It is, therefore, presumed that biochemical changes, namely the V646 (G1936) AKAP10 binding of PKA RIa with threefold greater affinity than the I646 variant, and increased targeting of the PKA RIa subunit to the mitochondria result in the observed association of the G1936 allele with mortality and morbidity in the adult population. 12 Both alleles are sustained in the population; the G allele is found in up to 37% alleles in people of European descent (i.e., Aboriginal Europeans), is less common in Asian populations (E16 to 20%), but is the major allele in Africans (E58 to 72%).…”
Section: Introductionmentioning
confidence: 99%